Manufatura aditiva e caracterização de componentes da liga Al-4,4%Mg utilizando diferentes processos de deposição metálica - CMT, PMC E PMC-MIX - Gomes, Bianca Ferreira (2018)
Among the several metallic additive manufacturing (MAM) technologies available, the wire-and-arc based ones are very beneficial due to the lower operational costs, higher efficiency use of raw materials, and high deposition rates achieved. The Cold Metal Transfer (CMT) process stands out by the lower heat input compared to the other wire-and-arc based methods. On the other hand, processes such as Pulse Multi Control (PMC) and its variants have not been tested yet in additive manufacturing and for this reason they should be evaluated. Therefore, considering the technologies potential and the need of automotive and aeronautical industry of manufacturing parts of complex and optimized geometry in a faster way, the study of these technologies is very relevant. Thus, the objective of this paper is the additive manufacturing of walls with Al-4,4Mg alloy using CMT, CMT-Pulse, PMC, PMC-Mix, and MIG-Pulse, and the evaluation of the regularity, hardness, mechanical strength, and porosity of the manufactured parts aiming future industrial applications. The results showed good mechanical properties, small pore fraction, and geometric uniformity of parts produced with PMC and PMC-Mix. PMC and MIG-Pulse parts presented the smaller pore fraction among the GMAW variants, although no difference was noticed in the mechanical properties of the parts.